1993
DOI: 10.1001/archinte.1993.00410200103013
|View full text |Cite
|
Sign up to set email alerts
|

Increased Osmolal Gap in Alcoholic Acidosis

Abstract: We studied a patient with alcoholic acidosis and an increased osmolal gap. Ethyl alcohol and other compounds that are known to increase serum osmolality in alcoholics were not detected. However, the levels of glycerol, acetone, and the acetone metabolites acetol and 1,2-propanediol were increased in the serum of this patient. On admission and 3 and 7 hours after admission, the combined serum osmolality of glycerol, acetone, acetol, and 1,2-propanediol accounted for 48%, 92%, and 62% of the increase in the osmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The concentration in this patient (2¢5 mmol/ L) is very high compared to a serum concentration of 0¢1-0 ¢ 5 mmol/ L found in patients with AKA or related condition. 14,17 Such a high concentration suggests that acetone and glycerol were present in much more signi¢cant quantities, as reported by Braden et al 12 The example presented in this paper demonstrates that the osmolar gap in AKA may not be as wide as was previously thought and it must therefore be used with caution as a diagnostic tool.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The concentration in this patient (2¢5 mmol/ L) is very high compared to a serum concentration of 0¢1-0 ¢ 5 mmol/ L found in patients with AKA or related condition. 14,17 Such a high concentration suggests that acetone and glycerol were present in much more signi¢cant quantities, as reported by Braden et al 12 The example presented in this paper demonstrates that the osmolar gap in AKA may not be as wide as was previously thought and it must therefore be used with caution as a diagnostic tool.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, in our case, the entire anion gap can be accounted for by the ketones. The nature of the gap remains largely obscure in most reported cases, 6,11 except in one case 12 where the anion gap was equal to the sum of b-hydroxybutyrate and lactate.…”
Section: Discussionmentioning
confidence: 95%
“…In a patient with an established metabolic acidosis from toxic alcohol ingestion, a normal or low osmolal gap can occur if blood is sampled after the volatile alcohols have been converted to the acid metabolites (59 ). Increases in the osmolal gap can occur in patients with multiple organ failure and other unmeasured osmolal entities (60,61 ), and can falsely suggest toxic alcohol exposure. A low osmolal gap is a poor discriminator as well.…”
Section: E Osmolality Measurements For Toxic Alcohol Surveillancementioning
confidence: 99%
“…On the other hand previous studies have found a close association between serum values of osmolality and ethanol [26]. In some patients with alcoholic acidosis the osmolal gap may not accurately reflect serum ethanol concentration [27].…”
Section: Discussionmentioning
confidence: 79%